ZrO2 functionalized graphene Oxide/SEBS‐Based nanocomposites for efficient electromagnetic interference shielding applications. (26th September 2018) - Zhao, Shuai; Sun, Pei Pei; Shao, Xiaoming; Liu, Xiaolin; Zhao, Zheng; Li, Lin; Xin, Zhenxiang
Abstract : ZrO2 ‐coated graphene oxide (GO)/SEBS(styrene‐ethylene‐butylene‐styrene)‐based nanocomposites were prepared for use as an electromagnetic interference (EMI) shielding material. Transmission electron microscopy (TEM) reveals almost every individual GO is fully and homogeneously covered with uniform ZrO2 . X‐ray diffraction (XRD) patterns and Differential scanning calorimetry (DSC) revealed increased ordering of ‐(CH2 ‐CH2 )n segments in the poly(ethylene‐ co ‐1‐butene) block of the SEBS matrix in the case of SEBS/ZrO2 ‐coated graphene oxide composites than in the SEBS/pristine graphene oxide nanocomposite. Thermogravimetric analysis (TGA) proved better oxidation resistance of SEBS/ZrO2 ‐coated GO nanocomposite compared to that of SEBS/pristine GO nanocomposite. The present nanocomposites exhibited excellent EMI shielding effectiveness (SE) over X‐band (8.2 GHz–12.4 GHz) with EMI SE of 37.9 dB. J. VINYL ADDIT. TECHNOL., 25:E130–E136, 2019. © 2018 Society of Plastics Engineers